Revisiting Mahmud Pasha Falaki’s Work on the Calendrical Practice of the Arabs and the Dates of the Prophetic Events - Shaikh, Fazlur Rehman (Islamic Studies, 2016)
Mahmud Pasha Falaki (1815–1885) argued that Arabian calendar of the lifetime of Prophet Mu╒ammad (peace be on him) was not an intercalating calendar but was purely a lunar calendar. Examining the intervals amongst three important dates of the lifetime of the Prophet, he arrives at a conclusion that the Arabian years were purely lunar years consisting of only twelve months and there was not such a thing as intercalary months. In lines with his such thinking, he contended that the Quranic word nasi was not postponement of the commencement of sacred months consequent to insertion of an additional month but was simply a deferment of the commencement of the sacred months from their due dates arising out of changing their names to those of other non-sacred ones. Of the calendrical practice of the Arabs, he propounds a probable model of the calendar that the Arabs could have used. But his model not only fails to disclose the reported biographical weekdays but also goes against his own Julian dates of the events. While he argues that the birth of the Prophet was in Rabi al-Awwal (i.e., April 571), his model throws up a Shaban against the same period of time. Similarly against his own contention that the Prophet emigrated in Rabi‘ al-Awwal (i.e., September 622), his model throws up a Shawwal against the same period. Further, none of the classical biographers reported 9 Rabi al-Awwal for the birthday of the Prophet. Hence the Julian date he proposed (i.e., April 20, 571), as corresponding to this date has no foundation to stand, despite its vast popularity among the modern writers.